WIAROŁOMNA NARZECZONA O PRAKTYCE MAŁŻEŃSKIEJ ZHELLENIZOWANEGO JUDAIZMU W ŚWIETLE ŹRÓDEŁ Z ŻYDOWSKIEJ DZIELNICY W HERAKLEOPOLIS (144/3 – 133/2 P.N.E.) - MÉLÈZE MODRZEJEWSKI, Józef (Zeszyty Prawnicze, 2017)
Unfaithful Bride The Matrimonial Practice of the Hellenistic Judaism in the Light of Sources from the Jewish Politeuma in Herakleopolis (144/3 – 133/2 BC) Summary The author is dealing with a Greek papyrus from Herakleopolis in Egypt where a Jewish politeuma is attested in the second half of the 2nd century BC (P.Polit.Iud. 4, 12 January 134 BC). This is a complaint by one Philotas, son of Philotas, a member of the politeuma, against Lysimachos, who had given his daughter Nikaia to him as a wife. After there Lysimachos changed his mind and gave his daughter to another man without receiving from Philotas the “customary bill of divorce” (to eithismenon tou apostasiou bublion). This document contributes to the discussion on the attitude of Hillel the Elder (Tosefta Ketubbot 4,9, and parallels) and Philo of Alexandria (De spec. leg. 3,72) concerning the legal situation of the spouses during the period separating the two stages of Jewish marriage, qiddushin and nissui’in. In the time of Philo and Hillel, the pregnancy of Mary (Matt. 1,18-25), the mother of Jesus, falls, from a judicial perspective, into the same category. Thanks to the Herakleopolis papyrus, the texts of Philo, Hillel and Matthew receive corroborating testimony from a source of unquestionable plausibility.